Inhibition of Xanthine Oxidase Protects against Sepsis-Induced Acute Kidney Injury by Ameliorating Renal Hypoxia. (15th July 2022) - Wang, Ting-ting; Du, Yi-wei; Wang, Wen; Li, Xiang-nan; Liu, Hong-bao
Abstract : Xanthine oxidase (XO) utilizes molecular oxygen as a substrate to convert purine substrates into uric acid, superoxide, and hydrogen peroxide, which is one of the main enzyme pathways to produce reactive oxygen species (ROS) during septic inflammation and oxidative stress. However, it is not clear whether XO inhibition can improve sepsis-induced renal hypoxia in sepsis-induced acute kidney injury (SI-AKI) mice. In this study, pretreatment with febuxostat, an XO-specific inhibitor, or kidney knockdown of XO by shRNA in vivo significantly improved the prognosis of SI-AKI, not only by reducing the levels of blood urea nitrogen, serum creatinine, tumor necrosis factor- α, interleukin-6, and interleukin-1 β in peripheral blood but also by improving histological damage and apoptosis, reducing the production of ROS, and infiltrating neutrophils and macrophages in the kidney. More importantly, we found that pharmacological and genetic inhibition of XO significantly improved renal hypoxia in SI-AKI mice by a hypoxia probe via fluorescence staining. This effect was further confirmed by the decrease in hypoxia-inducible factor-1 α expression in the kidneys of mice with pharmacological and genetic inhibition of XO. In vitro, the change in XO activity induced by lipopolysaccharide was related to the change in hypoxia in HK-2 cells. Febuxostat and XO siRNA significantly relieved the hypoxia of HK-2 cells cultured in 2% oxygen and reversed the decrease in cell viability induced by lipopolysaccharide. Our results provide novel insights into the nephroprotection of XO inhibition in SI-AKI, improving cell hypoxia by inhibiting XO activity and reducing apoptosis, inflammation, and oxidative stress.